An approximate analysis of the shortest queue policy on soft real-time scheduling. - Zhu, Weiping (Sigmetrics :performance evaluation review.)
The join the shortest queue (JSQ) policy is studied in the context of soft real-time scheduling. An approximate analysis of the JSQ is developed and presented in this paper. The result obtained from the approximate analysis is compared against the simulation one, that shows the approximate analysis is highly accurate. Thus, the approximate analysis can be applied to the development of soft real-time systems.